2018
DOI: 10.7150/ntno.26208
|View full text |Cite
|
Sign up to set email alerts
|

Clinically-Applicable Perfluorocarbon-Loaded Nanoparticles For In vivo Photoacoustic, 19F Magnetic Resonance And Fluorescent Imaging

Abstract: Photoacoustic imaging (PAI) is an emerging biomedical imaging technique that is now coming to the clinic. It has a penetration depth of a few centimeters and generates useful endogenous contrast, particularly from melanin and oxy-/deoxyhemoglobin. Indocyanine green (ICG) is a Food and Drug Administration-approved contrast agents for human applications, which can be also used in PAI. It is a small molecule dye with limited applications due to its fast clearance, rapid protein binding, and bleaching effect.Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 51 publications
0
43
0
Order By: Relevance
“…After intravenous (IV) injection, ICG rapidly binds albumin, establishing macromolecules that are unable to permeate the endothelium of many organs. In clinical field, ICG has been used for angiography, liver functional evaluation, and SLNs detection by FL and PA imaging, while in preclinical research, it has been proposed for monitoring tumor growth and therapeutic efficacy [24, 25]. PAI using ICG has been proven to provide early detection of neoangiogenesis in growing neoplasia such as a Lewis lung carcinoma mouse model, based on EPR effect exerted by ICG-albumin macromolecules within the tumor environment [26].…”
Section: Biomedical Pai Applications Based On Exogenous Optical Comentioning
confidence: 99%
See 1 more Smart Citation
“…After intravenous (IV) injection, ICG rapidly binds albumin, establishing macromolecules that are unable to permeate the endothelium of many organs. In clinical field, ICG has been used for angiography, liver functional evaluation, and SLNs detection by FL and PA imaging, while in preclinical research, it has been proposed for monitoring tumor growth and therapeutic efficacy [24, 25]. PAI using ICG has been proven to provide early detection of neoangiogenesis in growing neoplasia such as a Lewis lung carcinoma mouse model, based on EPR effect exerted by ICG-albumin macromolecules within the tumor environment [26].…”
Section: Biomedical Pai Applications Based On Exogenous Optical Comentioning
confidence: 99%
“…In vitro studies showed that the apoptotic effect of ICG after NIR irradiation is essentially mediated by heat and ROS generation, as confirmed in vivo by detection of tumor growth suppression in the Huh7 xenograft mouse model. Although ICG has been used to enhance the PA signal in tumor lesions, this simple contrast agent shows limited applications due to its lacks of specificity, rapid clearance, low photo stability, low water solubility, and tendency to form aggregates [24, 25]. Circulation time and photostability of ICG-based contrast agents have been improved through the encapsulation within NPs, for example, entrapping a high number of dye molecules into bigger NPs using the PEBBLE (photonic explorers for biomedical use by biologically localized embedding) technology.…”
Section: Biomedical Pai Applications Based On Exogenous Optical Comentioning
confidence: 99%
“…The encapsulation of ICG within NPs decreases its photobleaching and increases the retention of signals within the cells. It can detect as little as 0.1 × 10 6 cells in PAI and the nanocomplex [ 123 ]. Core–shell silica PEG NPs were developed with photothermal, photoacoustic, and NIR optical imaging properties.…”
Section: Medical Imagingmentioning
confidence: 99%
“…154 This work showed the potential of labeled primary human dendritic cells for cell imaging and lymph node detection with PAI and 19 F MRI. 155 Thus, 19 F MRI is an effective method of monitoring immune cell therapy.…”
Section: Drug Delivery and Therapy Efficacy Monitoringmentioning
confidence: 99%